Penegakan Hukum dalam Pelanggaran Administrasi Pemilihan Kepala Daerah di Indonesia - Sauri, Zaki Pratama (Lembaga Yasin AlSys, 2023)
This article discusses Law Enforcement in Violations of Regional Head Election Administration in Indonesia. The enforcement of the Election Law of the Head of Derah in relation to administrative violations is considered to need to be reviewed further, because the follow-up of the law enforcement of Administrative violations in regional head elections is the Recommendation of the Election Supervisory Agency (Bawaslu) on the results of the Review of administrative violations which then the General Election Commission (KPU) is obliged to follow up on the recommendations, but at the level of practice raises some legal problems. This study uses a qualitative method using a juridical approach. Data sources in the form constitution of laws that have been in force in Indonesia, including a few written works that have been published either in the form of books, journal articles, or in the form of existing research. This type of data is a statutory clause contained in a few of existing legal products and narratives contained in several published works. Data collection techniques by tracking published sources. Data analysis techniques are done descriptively. This article found that the effectiveness of electoral law in relation to follow-up recommunication of administrative violations of regional heads can only be obtained if the laws and regulations of regional head elections subtansi have subtansily met the standards of democratic election principles. From the findings above, this article provides recommendations to academics, Legal practitioners to further deepen the study of Law Enforcement in Violations of Regional Head Election Administration.